Narrative, nature, and the natural law from Aquinas to international human rights - Alford, Charles Fred (Palgrave Macmillan, 2010)
Introduction -- Saint Thomas : putting nature into natural law -- Maritain and the love for the natural law -- The new natural law and evolutionary natural law -- International human rights, natural law, and Locke -- Conclusion : evil and the limits of the natural law